2016
DOI: 10.1097/md.0000000000004356
|View full text |Cite
|
Sign up to set email alerts
|

Physiatrist referral preferences for postacute stroke rehabilitation

Abstract: This study was intended to determine if there is variation among physiatrists in referral preferences for postacute rehabilitation for stroke patients based on physician demographic characteristics or geography.A cross-sectional survey study was developed with 5 fictional case vignettes that included information about medical, social, and functional domains. Eighty-six physiatrist residents, fellows, and attendings were asked to select the most appropriate postacute rehabilitation setting and also to rank, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
(17 reference statements)
1
25
0
Order By: Relevance
“…Approximately 86.6% of the patients were referred to hospital/center-based settings to continue with physiotherapy. The results of the current study echo the study conducted by Cormier [29]. The authors reported that 73% of the older American stroke survivors receive institutional rehabilitation care.…”
Section: Rehabilitation Settingssupporting
confidence: 79%
“…Approximately 86.6% of the patients were referred to hospital/center-based settings to continue with physiotherapy. The results of the current study echo the study conducted by Cormier [29]. The authors reported that 73% of the older American stroke survivors receive institutional rehabilitation care.…”
Section: Rehabilitation Settingssupporting
confidence: 79%
“…This study builds on a prior study (Cormier et al, 2016) that used these same vignettes to conduct a survey of physiatrists' referral practices for the postacute stroke population. The surveys used in the physician study and in the current study were nearly identical, except that the collected demographic information was adjusted to reflect the target population.…”
Section: Discussionmentioning
confidence: 99%
“…The remainder of the survey asked the respondents to select the most appropriate postacute level of care for each of five acute stroke survivors, presented in the form of case vignettes with the assumption that each patient was being treated in a stroke unit after suffering an acute stroke and that the referral decision was made within a week after stroke. The five case vignettes (see Table 1) were the same as those used in a similar study examining postacute stroke care referral patterns of physiatrists (Cormier, Frantz, Rand, & Stein, 2016). The cases were written to represent relatively common scenarios encountered in acute care hospitals surrounding appropriate discharge plans for patients after acute stroke.…”
Section: Survey Designmentioning
confidence: 99%
“…Patients' mental status 23,25,[27][28][29][30][32][33][34][35] as well as patients' energy and drive (e.g., motivation) 10,23,25,[27][28][29][30]32,34,35 are other frequently reported factors. Both affect patients' ability to engage in rehabilitation and make functional gains 23,25,32 .…”
Section: Pre and Post-stroke Characteristicsmentioning
confidence: 99%